The Learning Curve of Da Vinci Robot-Assisted Hemicolectomy for Colon Cancer: A Retrospective Study of 76 Cases at a Single Center - Huang, Pu; Li, Sen; Li, Peng; Jia, Baoqing (Frontiers in Surgery, 2022)
Background and Aims: Robotic-assisted right hemicolectomy (RARH) has many benefits in treating colon cancer, but it is a new technology that needs to be evaluated. This study aims to assess the learning curve (LC) of RARH procedures with the complete mesoscopic exception and D3 lymph node dissection for colon carcinoma. Methods: A retrospective analysis was performed on a consecutive series of 76 Patients who underwent RARH from July 2014 to March 2018. The operation time was evaluated using the cumulative sum method to analyze the LC. The patients were categorized into two groups based on the learning curve: Phase I and Phase II. Statistical methods were used to compare clinicopathological data on intraoperative and perioperative outcomes at different stages of the study. Results: The peak point of the learning curve was observed in the 27th case. Using the cumulative sum method, we divide the learning curve into two stages. Stage 1 (initial learning stage). Cases 1 to 27; Phase 2 (proficiency phase). Cases 28 to 76. There were no obvious distinctions between the two patients' essential characteristics (age, sex, BMI, clinical-stage, ASA score). The mean operation time of each group is 187.37 ± 45.56min,161.1 ± 37.74 min (P=0.009). Respectively, the intraoperative blood loss of each group is 170.4 ± 217.2ml, 95.7±72.8 (P=0.031). Conclusions: Based on the learning curve with CUSUM analysis, the data suggest that the learning phase of RARH was achieved after 27 cases. The operation time and the intraoperative blood loss decrease with more cases performed.